A new remarkable short-tailed whip-scorpion species of Piaroa (Arachnida, Schizomida, Hubbardiidae) from the Colombian Caribbean region - Segovia-Paccini, Alejandro; Ahumada-C., Daniela; Moreno-González, Jairo A. (Zootaxa, 2018)
Herein, we describe a new schizomid species from the genus Piaroa Villarreal, Giuponni & Tourinho, 2008, Piaroa turbacoensis sp. nov., based on individuals collected in the Botanical Garden “Guillermo Piñeres”, Turbaco, Bolivar, Colombian Caribbean region. Piaroa turbacoensis is the sixth species of the genus to be found in Colombia, and the tenth to be found with regards to the genus as a whole. This species is the first Colombian species to be recorded in a Dry Tropical Forest biome. Piaroa turbacoensis is easily distinguishable by the presence of spermathecae lateral lobes with massive circular stalk bases, and male pedipalp with ventroectal truncate process over the femur and ventroectal depression over the patella. Here, we provide an updated distribution map of the genus and comments about the natural history of the new species.